https://doi.org/10.36873/ PENGARUH DOSIS UREA DAN UMUR DEFOLIASI PERTAMA TERHADAP JUMLAH ANAKAN, PANJANG DAUN DAN BOBOT SEGAR RUMPUT GAJAH (Pennisetum purpureum Schumach.) PADA TANAH LATOSOL: The Effect of Urea Dose and First Defoliation Age on Buds Amount, Lenght Leaves and Fresh Weight of Elephant Grass (Pennisetum purpureum Schumach.) in Latosol Soil - Satrio Wibowo; D Latifudin (Fakultas Pertanian Universitas Palangka Raya, 2021)
Study which mean to knowed the effect of urea dose and age of first defoliation on amount of buds, leaves length and freshweight of elephant grass have done in latosol soil in Jatinangor District, Sumedang Residence, West Java. The research made randomized block design with 3x3 factorial pattern with three repetition. First treatment factor was three doses of urea (175, 200 and 225 kgha-1) and the second was first age of defoliation (40, 50 and 60 days). SP-36 and KCl fertilizers was given 100 kgha-1 respectively, without given compose fertilizer and lime. The research was showed only single factor that first defoliation age which influenced on amount of buds and freshweight of the grass, but there was influenced interaction of urea dose with first defoliation age on the length leaves significantly. Amount of the buds in 60 days defoliation age (8,48) was higher than 50 days (5,74) and 40 days (4,48) highly significantly. The highest of the grass length leaves were found from interaction of 175 kgha-1 urea with 60 days defoliation age (46,68 cm) followed 200 kgha-1 urea with 60 days defoliation (44,96 cm), 225 kgha-1 urea with 50 days defoliation (43,57 cm), 200 kgha-1 urea with 40 days age (38,79 cm), 225 kgha-1 urea with 60 days age (37,73 cm) and 175 kgha-1 urea with 50 days (37,32 cm). The grass freshweight on 60 days first defoliation age (163,92 gm-2) higher than the 50 days (102,45 gm-2) and 40 hari (28,98 gm-2).